2014
DOI: 10.1002/adem.201400133
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the ZrO Phase at Zirconium/Zirconium Oxide Interfaces

Abstract: Zirconium-based alloys are used in water-cooled nuclear reactors for both nuclear fuel cladding and structural components. Under this harsh environment, the main factor limiting the service life of zirconium cladding, and hence fuel burn-up efficiency, is water corrosion. This oxidation process has recently been linked to the presence of a sub-oxide phase with well-defined composition but unknown structure at the metal–oxide interface. In this paper, the combination of first-principles materials modeling and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
37
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 28 publications
2
37
0
1
Order By: Relevance
“…Additionally, to confirm that the contrast change is not induced by mechanical contact with the W tip, a series of experiments were carried out (see Figure S4 and Movie S4, Supporting Information). We suggest that the crystallographic similarity between the cubic TiN metal and cubic ZrO structures is the reason that this phase forms, similar to the hexagonal Zr metal and hexagonal ZrO structures reported by Nicholls et al It should be noted that the charging behavior and the electron beam shower have the negligible impact on in situ test results, as shown in Figure S5 in the Supporting Information. Defect generation is more severe at the interface than at other locations, and the theoretical calculation is given in Figures S6 and S7 in the Supporting Information.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…Additionally, to confirm that the contrast change is not induced by mechanical contact with the W tip, a series of experiments were carried out (see Figure S4 and Movie S4, Supporting Information). We suggest that the crystallographic similarity between the cubic TiN metal and cubic ZrO structures is the reason that this phase forms, similar to the hexagonal Zr metal and hexagonal ZrO structures reported by Nicholls et al It should be noted that the charging behavior and the electron beam shower have the negligible impact on in situ test results, as shown in Figure S5 in the Supporting Information. Defect generation is more severe at the interface than at other locations, and the theoretical calculation is given in Figures S6 and S7 in the Supporting Information.…”
supporting
confidence: 82%
“…The partial crystallization of the ZrO 2 film is of particular interest; as shown in Figure f–g, the fast Fourier transform (FFT) patterns show that the area after breakdown is cubic ZrO, while the initial ZrO 2 phase is monoclinic before breakdown. There is no known stable bulk ZrO phase, and so far, none have been reported in the literature by an unambiguous experiment . Nicholls et al reported a hexagonal ZrO phase resulting from the oxidation of zirconium alloys; however, the formation of hydrides is questionable.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…17 Atomistic structure prediction techniques have been developed [18][19][20][21][22][23][24][25][26] and widely applied to many important structural problems [27][28][29] . We developed CALYPSO (Crystal structure AnaLYsis by Particle Swarm Optimization) for structure prediction.…”
Section: Introductionmentioning
confidence: 99%
“…The tetragonal ZrO 2 can be considered as a slightly distorted cubic structure (see Figure 3(b)). In the crystalline tetragonal structure of ZrO 2 , zirconium atoms are also bound to eight oxygen atoms-four neighboring oxygen atoms are located at the tetrahedron plane with a Zr-O bond length of 0.207 nm, while the other oxygen atoms are located at a 90°angle to the tetrahedron plane at a distance of 0.246 nm from the zirconium atoms [19,20]. The monoclinic ZrO 2 is formed by further distortion of the tetragonal structure (see Figure 3(c)).…”
Section: Crystallochemical Characteristics Of Metalmentioning
confidence: 99%